Novel technologies can provide effective dressing and securement for peripheral arterial catheters: A pilot randomised controlled trial in the operating theatre and the intensive care unit. Issue 3 (August 2015) - Reynolds, Heather; Taraporewalla, Kersi; Tower, Marion; Mihala, Gabor; Tuffaha, Haitham W.; Fraser, John F.; Rickard, Claire M.
Abstract Background Peripheral arterial catheters are widely used in the care of intensive care patients for continuous blood pressure monitoring and blood sampling, yet failure – from dislodgement, accidental removal, and complications of phlebitis, pain, occlusion and infection – is common. While appropriate methods of dressing and securement are required to reduce these complications that cause failure, few studies have been conducted in this area. Objectives To determine initial effectiveness of one dressing and two securement methods versus usual care, in minimising failure in peripheral arterial catheters. Feasibility objectives were considered successful if 90/120 patients (75%) received the study intervention and protocol correctly, and had ease and satisfaction scores for the study dressing and securement devices of ≥7 on Numerical Rating Scale scores 1–10. Methods In this single-site, four-arm, parallel, pilot randomised controlled trial, patients with arterial catheters, inserted in the operating theatre and admitted to the intensive care unit postoperatively, were randomly assigned to either one of the three treatment groups (bordered polyurethane dressing (n = 30); a sutureless securement device (n = 31); tissue adhesive (n = 32)), or a control group (usual practice polyurethane dressing (not bordered) (n = 30)). Results One hundred and twenty-three patients completed the trial. The primary outcome of catheter failure was 2/32 (6.3%) for tissue adhesive, 4/30 (13.3%) for bordered polyurethane, 5/31 (16.1%) for the sutureless securement device, and 6/30 (20%) for the control usual care polyurethane. Feasibility criteria were fulfilled. Cost analysis suggested that tissue adhesive was the most cost effective. Conclusions The pilot trial showed that the novel technologies were at least as effective as the present method of a polyurethane dressing for dressing and securement of arterial catheters, and may be cost effective. The trial also provided evidence that a larger, multicentre trial would be feasible.